Use of Real-World Contexts in Instructional Materials Designed by Pre-University Mathematics Teachers - Tan, Zheng Han, Hans; Lam, Toh Tin; Fah, Lay Yoon (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2023)
Pre-university education in Singapore serves as a bridge between secondary and university education. Despite its importance and the popularity of mathematics as a subject, few studies have been conducted on Singapore pre-university mathematics. We also notice that problems in real-world contexts have been increasingly emphasised in the Singapore mathematics curriculum. In this paper, we study the infusion of real-world contexts in the instructional materials of a typical pre-university institution, with a focus on the topic of vectors. The word problems used in the instructional materials involving real-world contexts are categorised into neutral contexts and basic real-life experiences, and the benefits of utilising these problems are discussed. The benefits include the potential to raise students’ awareness that mathematics can be used as a resource to solve real-world problems or explain real-world phenomena. The alignment of these word problems to the Singapore mathematics curriculum and 21st Century Competencies is also discussed.